2016
DOI: 10.1097/qai.0000000000000868
|View full text |Cite
|
Sign up to set email alerts
|

Reversibility of Glomerular Renal Function Decline in HIV-Uninfected Men and Women Discontinuing Emtricitabine-Tenofovir Disoproxil Fumarate Pre-Exposure Prophylaxis

Abstract: Background Tenofovir disoproxil fumarate (TDF) pre-exposure prophylaxis (PrEP) use is associated with a small but statistically significant decline in estimated glomerular filtration rate (eGFR). We investigated the reversibility of eGFR decline among HIV-uninfected adults discontinuing PrEP. Methods Data were from the Partners PrEP Study, a randomized trial of daily oral TDF and emtricitabine (FTC)-TDF PrEP among African HIV-uninfected men and women with baseline creatinine clearance ≥60mL/min. Serum creati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(45 citation statements)
references
References 25 publications
2
42
1
Order By: Relevance
“…Previously, there have been a few case reports describing the reversal of ADV and TDF-related Fanconi's syndrome after TDF withdrawal in patients with CHB [12,26]. In contrast, our study showed that nucleotide analogue-related PRTD could be resolved in 16 CHB patients after discontinuation of nucleotide analogue similar to the phenomenon that occurs in HIV-infected patients [21][22][23][24][25]. The complete reversal of nucleotide analogue PRTD occurred in 81% of the patients at one year.…”
Section: Discussioncontrasting
confidence: 45%
See 2 more Smart Citations
“…Previously, there have been a few case reports describing the reversal of ADV and TDF-related Fanconi's syndrome after TDF withdrawal in patients with CHB [12,26]. In contrast, our study showed that nucleotide analogue-related PRTD could be resolved in 16 CHB patients after discontinuation of nucleotide analogue similar to the phenomenon that occurs in HIV-infected patients [21][22][23][24][25]. The complete reversal of nucleotide analogue PRTD occurred in 81% of the patients at one year.…”
Section: Discussioncontrasting
confidence: 45%
“…In contrast to these studies [4][5][6]17], PRTD and impaired phosphate renal tubular reabsorption were seen in 15-48% of CHB patients receiving long-term ADV and TDF therapy as in real world clinical experience [8,10,[18][19][20]. Reversibility of renal dysfunction has been shown in HIV-infected patients after cessation of TDF [21][22][23][24][25]. A few cases of reversible TDF or ADV-induced PRTD and Fanconi's syndrome have been reported in CHB patients after stopping treatment with nucleotide analogues [12,26].…”
Section: Introductionmentioning
confidence: 69%
See 1 more Smart Citation
“…The incidence of serious renal events in PrEP trials has been low. Moreover, in iPrEx and Partners PrEP, declines in renal function were mostly reversible 4–20 weeks after discontinuation 3,7 .…”
Section: Introductionmentioning
confidence: 97%
“…TDF, alone or with FTC, when used as PrEP is generally safe and well tolerated. Small but nonprogressive decreases in estimated creatinine clearance levels and decreases in bone mineral density can occur in a minority of persons taking TDF as PrEP but these quickly resolve within weeks of discontinuing PrEP (2326). …”
Section: Mechanism Of Action and Clinical Pharmacologymentioning
confidence: 99%